EVOLUSI KURIKULUM SEKOLAH DASAR DI INDONESIA DARI MASA KE MASA - Syudirman; I Wayan Suastra; I Wayan Lasmawan (YAYASAN CENDEKIA CITRA GEMILANG, 2025)
This research explores the evolution of the primary school curriculum in Indonesia over time, with the aim of understanding how social changes, cultural and scientific developments affect curriculum design and implementation. From the beginning of independence, curricula tended to be rigid, focusing on content mastery and memorization. Over time, especially after reformasi, there has been a significant shift towards a more flexible and competency-oriented curriculum that emphasizes character development, 21st century skills and relevance to the local context. This research found that modern curricula, such as Curriculum 2013, integrate a holistic approach that links knowledge, skills and attitudes, creating more meaningful learning experiences for students. The findings show the importance of continuous curriculum evaluation and renewal to face global challenges and create inclusive and quality education in the future.